2010
DOI: 10.1007/s10751-010-0218-z
|View full text |Cite
|
Sign up to set email alerts
|

Observation of iron impurity diffusion in silicon under bending stress by Mössbauer spectroscopy

Abstract: External bending stress was applied to a 57 Fe-doped n-type silicon wafer, and transmission Mössbauer spectra were measured at room temperature in order to observe directly stress induced diffusion of 57 Fe atoms in the silicon matrix. As the stress is increased up to 23 MPa, the resonance area of the substitutional Fe s component is found to decrease by more than 30%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…The isomer shift, which is proportional to the electron density at the nucleus, corresponds to the energy shift of the nuclear level for a Mössbauer component on a Doppler velocity scale of mm/s against the spectral centre of α-Fe at room temperature. The data have been obtained in different Mössbauer experiments on 57 Fe impurities, which were differently introduced into Si samples, and subsequently measured at different temperatures: (1) deposition at room temperature, and diffusion and measurements at high temperatures up to 1273K [11,14,15], (2) highly energetic implantation of the mother isotope of 57 Mn/ 57 Fe into Si [12,13,17], and (3) deposition and diffusion, and measurements at room temperature [16,[18][19][20]. All the results can be analysed by the new model based on the interstitial Fe with neutral, +1, and + 2 states (defect associated), in addition to substitutional Fe with neutral, possibly +1 and -1 states.…”
Section: A Model For Fe Components Observed In Mössbauer Spectramentioning
confidence: 99%
See 1 more Smart Citation
“…The isomer shift, which is proportional to the electron density at the nucleus, corresponds to the energy shift of the nuclear level for a Mössbauer component on a Doppler velocity scale of mm/s against the spectral centre of α-Fe at room temperature. The data have been obtained in different Mössbauer experiments on 57 Fe impurities, which were differently introduced into Si samples, and subsequently measured at different temperatures: (1) deposition at room temperature, and diffusion and measurements at high temperatures up to 1273K [11,14,15], (2) highly energetic implantation of the mother isotope of 57 Mn/ 57 Fe into Si [12,13,17], and (3) deposition and diffusion, and measurements at room temperature [16,[18][19][20]. All the results can be analysed by the new model based on the interstitial Fe with neutral, +1, and + 2 states (defect associated), in addition to substitutional Fe with neutral, possibly +1 and -1 states.…”
Section: A Model For Fe Components Observed In Mössbauer Spectramentioning
confidence: 99%
“…Mössbauer spectroscopy appears to be ideal to characterize Fe impurities in Si crystal [6][7][8][9][10]. Recently, we have performed a series of the experimental investigations [10][11][12][13][14][15][16][17][18][19][20] using Mössbauer spectroscopy on Fe impurities in p-type and n-type Si materials such as single crystal Si, multi-crystal line (mc) Si wafers, and even mc-Si solar cells, the results are appealing that we need a new picture for Fe impurities in Si materials: the Fe impurities in the Si matrix exist not only on the interstitial sites with Fe int 0/+ and Fe int + -Bpair, but also on a higher charge state of Fe int 2+ associated with defects as well as on the substitutional sites with Fe sub 0 and Fe sub -. Furthermore, these components are found to transform each other in the Mössbauer spectra by changing experimental conditions such as temperature, external voltage, electron or light irradiation, and external stress as well as by changing the Fermi level, carriers and their concentrations, and the device structures in the vicinity of 57 Fe probes.…”
Section: Introductionmentioning
confidence: 99%
“…So far, the "interstitial" iron mapping has been considered to be possible by µ-PCD and Photo-Luminescence (PL), and the analysis was based on a Zoth and Bergholz model [1], which took into account of the measurements of the carrier life time before and after breaking Fe-B pairs in B-doped p-type Si. However, a series of the experimental investigations using Mössbauer spectroscopy on Fe impurities in single crystal Si [2], in multi-crystal Si wafers, and even in mc-Si solar cells [3][4][5][6] have recently revealed that the Fe impurities in the Si matrix exist not only on the interstitial sites with Fe i 0/+ and Fe i + -Bpair, but also on an interstitial site with a higher charge state of Fe i 2+ as well as on the substitutional sites with Fe s 0 and Fe s - [6]. Furthermore, these components transform each other by changing external conditions.…”
mentioning
confidence: 99%
“…We have performed 57 Fe Mössbauer experiments under different experimental conditions such as at high temperatures [2][3][4], under applying external stresses [5], under light illumination [6], and under applying external voltages as well. If a charge fluctuation between the different charge states of Fe atoms would occur within a life time of 100 ns due to the carrier trappings on the Fe impurities, the spectrum might show "a motional averaging" of the Fe components, which could provide a possibility to determine the carrier trapping cross sections corresponding to the Fe components.…”
mentioning
confidence: 99%
See 1 more Smart Citation